HUBUNGAN ANTARA KEMAMPUAN MENGHAFAL AL QUR’AN TERHADAP KECERDASAN MATEMATIS LOGIS SANTRI MA’HAD BUSTANUL QUR’AN ASSURYANIYAH BEKASI - Budiono, Imam; Khoir, Abdul (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2023)
This study tries to ascertain the connection of student logical-mathematical on the ability of memorizing the Al-Qur'an. Correlational research using a quantitative technique includes this kind of study. 60 students muslim were chosen for the research sample using a straightforward random sampling proceduct. Research data were collected via tests, and documentation; these data were then checked fornormality, homogenity and linearity before being subjected to a straightforward Pearson Correlation analisys. The study's findings indicated that memorizing the Qur'an intensely positifity impact. Proof of the all that output signifikasi 0,000 < 0,05 Pearson Correlation 0,818 > 0,05 t value a caunt 0,254 < 0,818. meaning that the more ability memorized the Qur'an, the better one's logical-mathematical intelligence.